The effect of intravitreal injection of anti-VEGF drugs on the ophthalmotonus values in patients with classic and occult choroidal neovascularization - A.V. Kuroyedov; Zakharova M.A.; O.V. Gapon’ko; V.V. Gorodnichiy (РМЖ "Клиническая офтальмология")
Kuroyedov A.V.1,2, Zakharova M.A.3, Gaponko O.V.1, Gorodnichy V.V.1 1 Central Military Clinical Hospital named after P. V. Mandryka, Moscow 2 Pirogov Russian National Research Medical University, Moscow 3 S. Fyodorov Eye Microsurgery Federal State Institution, Moscow Aim: to study the changes in the level of intraocular pressure (IOP) in the early period after the intravitreal administration of anti-VEGF drugs in patients with classical and occult choroidal neovascularization (CNV). Patients and Methods: 34 patients (40 eyes) with age-related macular degeneration were divided into 2 groups. Group 1 — the patients (19 eyes) with classic CNV, group 2 — the patients (21 eyes) with occult CNV. In all patients the IOP were measured an hour before the treatment, on the 7-th day after the injection of ranibizumab and at the 1-month follow-up visit. Results: in group 1 the level of IOP increased an hour after the injection, but on the 7th day it was already at the initial level, which persisted after 1 month (p>0,05). In the second group, the IOP level remained stable throughout the follow-up period  (p <0.05). Differences in the level of IOP in an hour, on the 7th day and 1 month after intravitreal injection in patients of both groups and between groups were not detected (p> 0.05). There was no significant difference in retinal thickness before and after intravitreal injection in both groups (p> 0.05). However, significant difference was noted in patients of both groups in corrected visual acuity before and after treatment (p<0.05). Conclusions: in patients with a classical choroidal neovascularization, an increase in the IOP level was observed one hour after the intravitreal administration of anti-VEGF drugs. The difference in the IOP-level in patients with age-related macular degeneration in the group with classical CNV and in the group with occult CNV after intravitreal injection of the anti-VEGF was not detected in an hour, on the 7th day and 1 month after the administration of the anti-VEGF preparation. Key words: anti-VEGF drugs, IOP-level, choroidal neovascularization, age-related macular degeneration. For citation: Kuroyedov A.V., Zakharova M.A., Gaponko O.V., Gorodnichy V.V. The effect of intravitreal injection of anti-VEGF drugs on the ophthalmotonus values in patients with classic and occult choroidal neovascularization.  RMJ “Clinical ophthalmology”. 2018;2:102–106.